Bio-Chemical Composition of Some Walnut (Juglans Regia L.) Genotypes of North-Western Himalayan Region (Bangladesh Journal of Botany, 2022)
Fifteen autochthonous walnut (Juglans regia L.) genotypes of the North-western Himalayan region were evaluated for biochemical composition. The moisture content in them ranged from 2.98 to 8.69 % whereas, the oil content varied from 40.00 to 62.43 %. The linoleic acid was found most abundant among the fatty acids values which ranged between 48.50 and 67.30 %. Furthermore, linolenic acid and oleic acid content ranged from 5.70 to 18.58% and 12.14 to 20.60 %. The protein and carbohydrate content extended from 15.00 to 23.00% and 9.03 to 12.96 g/100 g, respectively. Vitamin B1 was the amplest vitamin ranging from 0.74 to 0.52 mg/100g. Results of the present study revealed that the genotype JWSD-59 contained highest percentage of fats, oils and nutrients and genotype JWSP-06 in proteins. These genotypes can be utilized for breeding of nutrient rich cultivars and serve as reserve gene pool for the future walnut improvement programme efforts.Bangladesh J. Bot. 51(1): 93-101, 2022 (March)